Effect of family control on corporate dividend policy of firms in Pakistan - Imran Yousaf; Shoaib Ali; Arshad Hassan (Financial Innovation, 2019)
This study examines the impact of family control on the dividend policy of firms in Pakistan, covering the period from 2009 to 2016. It also investigates whether family control moderates the impact of firm-specific factors on the dividend policy. The GMM model for panel data estimation is used. The mean difference univariate analysis shows that family firms differ from nonfamily firms based on financial characteristics. The multivariate analysis shows that family firms pay lower dividends than nonfamily firms. Besides, firm size inversely affects the dividend policy, whereas tangibility positively affects it. Moreover, family control does not moderate the impact of all firm-specific factors on the dividend policy. Overall, family control, size, and tangibility are found to be the main determinants of the dividend policy in Pakistan.
Keywords: 650; Family firm; Family ownership; Dividend; Minority shareholder; Expropriation; Agency conflicts